해양경찰 제2교육훈련기관 설립 필요성 및 설립기준 연구 - 고명석 (한국해양경찰학회보, 12(2), 2022)
해양경찰 업무는 해양에서 집행적 업무로서 종합성, 다기능성, 전문성, 기술성의 특성을 가진다. 이에 따라 해양경찰에서 실시하는 교육훈련에서도 특징이 나타난다. 즉, 바다 환경에 대한 이해를 넓히는 교육이 필요하고, 이질적이고 다양한 업무로 인해 각 업무에 대한 전문성을 키우기가 어려우며, 업무수행 능력을 일정한 수준까지 향상시키기까지 장기간이 소요된다. 교육내용도 기술적이고 실습 중심으로 이루어질수 밖에 없다. 이런 업무특성을 반영한 교육훈련 설계가 필요한데, 현실의 해양경찰 교육훈련은 미흡한 점이 있다. 해양경찰 교육훈련은 해양경찰교육원에서 주로 실시되는데, 교육 기관 설립의 역사가 짧고, 신임과정과 재직자과정이 장소적 측면에서나 프로그램 측면에서 통합형태로 운영되어 왔다. 양질의 강사 및 전국적 교육생의 접근하기에 지리적 입지조건도 좋지 않다. 본 연구는 해양경찰 교육훈련 중에서 해양경찰교육원의 교육훈련을 중심으로 유사 교육훈련기관과 비교하여 진단해 보고자한다. 신임과정과 재직자과정을 통합적으로 운영하는 해양경찰 교육훈련이 가지는 구조적인 문제점을 도출해보고, 문제점을 해결할 수 있는 구조적·거시적 대안을 제시해 보고자 한다. 이에 따라 현행 해양경찰 교육훈련을 전면적으로 해결하는 방안으로서 해양경찰 제2교육훈련기관 설립이 필요함을 제시해 보겠다. 또 조직 및 소요인력, 교육프로그램, 시설·장비, 입지 등 여러 측면에서 해양경찰 제2교육훈련기관 설립기준을 제시해 보고자 한다. Coast Guard work is an executive work in the sea and has the characteristics of comprehensiveness, multifunctionality, expertise, and technology. Accordingly, characteristics appear in education and training conducted by Coast Guard. In other words, education to broaden understanding of the sea environment is necessary, it is difficult to develop expertise in each task due to heterogeneous and diverse tasks, and it takes a long time to improve work performance to a certain level. The educational content is also technical and centered on practice. Education and training design reflecting these work characteristics is necessary, but the actual Korea Coast Guard education and training is insufficient. Korea Coast Guard education and training are mainly conducted at the Korea Coast Guard Academy, and the history of establishing educational institution is short, and newcomer and incumbent courses have been operated in an integrated form in terms of its location and educational program. The geographical location conditions are also not good for access to quality instructors and nationwide trainees. This study aims to diagnose Coast Guard education and training by comparing it with similar education and training institutions, focusing on the education and training of the Korea Coast Guard Academy. I would like to derive structural problems of Coast Guard education and training, which operate the new comer course and the incumbent course in an integrated manner, and propose structural and macro alternatives to solve the problems. Accordingly, I will suggest that the establishment of second education and training institution of the Korea Coast Guard is necessary as a way to completely solve the current education and training. In addition, we would like to present the criteria for establishing a second education and training institution for the the Korea Coast Guard in various aspects such as organization, manpower required, educational programs, facilities, equipment, and location. KCI Citation Count: 0